Effects of Italian Mediterranean Organic Diet on the Gut Microbiota: A Pilot Comparative Study with Conventional Products and Free Diet - Laura Di Renzo; Giulia Frank; Barbara Pala; Rossella Cianci; Giada La Placa; Glauco Raffaelli; Roselisa Palma; Daniele Peluso; Antonino De Lorenzo; Paola Gualtieri; on behalf of Clinical Nutrition and Nutrigenomics Project Group (Microorganisms, 2025)
The human exposome, including dietary exposures such as pesticides, additives, and environmental contaminants, plays a critical role in shaping the gut microbiota (GM) and long-term health outcomes. While the Mediterranean Diet is known for its health-promoting effects, the role of food quality, specifically organic vs. conventional products, in modulating GM within this dietary pattern remains underexplored. The aim of this study was to evaluate (1) whether an Italian Mediterranean Organic Diet (IMOD) confers additional benefits compared to an Italian Mediterranean non-Organic Diet (IMnOD), and (2) the impact of IMOD and IMnOD versus a free diet (No Diet) on GM and anthropometric parameters. A randomized, controlled trial was conducted on 39 healthy subjects. Eligible subjects were divided into the following groups: (1) 4 weeks No Diet, (2) 4 weeks IMOD, and (3) 4 weeks IMnOD. Microbiota profiling (16S rRNA sequencing), body composition (BIA), and dietary adherence (MEDAS, FFQ) were evaluated. Distinct microbial shifts following both IMOD and IMnOD compared to No Diet were revealed. Several taxa previously associated with short-chain fatty acid (SCFA) biosynthesis (i.e., Anaerobutyricum hallii, Anaerostipes hadrus, and Dorea longicatena) were increased after both Mediterranean Diet interventions, while Parabacteroides distasonis showed a specific increase in the IMOD group. No significant changes in body weight or composition were observed. These findings suggest that adherence to a Mediterranean Diet, regardless of food source, reshapes the gut microbiota, while organic food intake may influence specific microbial trajectories. Our results support the relevance of food quality in dietary interventions.